Human papillomavirus vaccination intention among young women in Thailand - Juntasopeepun,P. (Asian Pacific Organization for Cancer Prevention, 2015)
Aims: The aims of this study were to examine knowledge and beliefs regarding HPV and cervical cancer and to predict HPV vaccination intention among young women in Thailand using a cross-sectional descriptive study design. Methods: A sample of young women aged 18-24 years (n = 391) were recruited from universities/colleges located in Chiang Mai, Thailand. An online survey was carried out to obtain young women's demographic, HPV and cervical cancer-related health characteristics, knowledge, and beliefs toward HPV and cervical cancer. Multivariate logistic regression analysis was used to determine significant independent predictors of HPV vaccination intention. Findings: Five participants (1.2%) had received at least one shot of the HPV vaccine. Of 386 participants, 218 (56.5%) reported high intention to obtain the HPV vaccine. Young women's knowledge about HPV and cervical cancer was moderate. The mean knowledge score was 7.89 (SD, 3.99; range, 0-15). Knowledge was significantly and positively related to perceived susceptibility, perceived seriousness, and perceived benefits of HPV vaccination, but negatively related to perceived barriers to HPV vaccination. Participants with a higher level of knowledge were significantly more likely to obtain the vaccine. A multivariate logistic regression model identified predictors of HPV vaccination intention: recommendations from significant others, perceived susceptibility, perceived benefits, and feeling embarrassed about getting the HPV vaccine. Conclusions: Health education efforts are needed to promote further understanding of HPV and cervical cancer, particularly with more attention to the HPV vaccination.